2-Butyl-5-pentyl-benzene-1,3-diol - Juangjun Jumpathong (2018)
In the title compound, C15H24O2, a natural dialkyl-resorcinol commonly named stemphol, the mol-ecules are linked into C(6) and C 2 2(4) chains and R 4 4(16) rings by inter-molecular O - H⋯O hydrogen bonds, creating mol-ecular sheets parallel to the (010) plane. The alkyl chains are directed orthogonally away from these planes in almost complete extension.